Librarians Technology Skills and Management of Electronic Information Resources in University Libraries in South-South Nigeria - Dime, Ishioma Angela; Akporhonor, Blessings Amina; Ogbomo, Esoswo Francisca (Edulib, 2024)
This study investigated librarians technology skills and management of electronic information resources in university libraries in south-south Nigeria. Three research questions were developed, and one null hypothesis was formulated in relation to what the study sought to find out. A structured Questionnaire entitled Librarians’ Technology Skills and Management of Electronic Information Resources Questionnaire” (LTSMEIRQ) was developed and used for data collection while three experts were engaged to validate the instrument. The reliability coefficient of the instrument was found to be 0.97 using Person Product Moment Correlation Coefficient. The questionnaire was used for collecting data from 242 respondents made of librarians in University libraries in South-South Nigeria. The data collected were analyzed using descriptive and inferential to answer the raised research questions and the formulated hypothesis. The study affirmed that librarians in University libraries in South-South Nigeria possessed high level technology skills, also the study found that relationship exists between librarians technology skills and management of electronic information resources in university libraries in south-south Nigeria. The study recommended constant upskilling and reskilling of librarians in the University to remain relevant in the scheme of global development.